HSP90 identified by a proteomic approach as druggable target to reverse platinum resistance in ovarian cancer. Issue 4 (19th January 2021) - Lombardi, Rita; Sonego, Maura; Pucci, Biagio; Addi, Laura; Iannelli, Federica; Capone, Francesca; Alfano, Luigi; Roca, Maria Serena; Milone, Maria Rita; Moccia, Tania; Costa, Alice; Di Gennaro, Elena; et al.
Abstract : Acquired resistance to platinum (Pt)‐based therapies is an urgent unmet need in the management of epithelial ovarian cancer (EOC) patients. Here, we characterized by an unbiased proteomics method three isogenic EOC models of acquired Pt resistance (TOV‐112D, OVSAHO, and MDAH‐2774). Using this approach, we identified several differentially expressed proteins in Pt‐resistant (Pt‐res) compared to parental cells and the chaperone HSP90 as a central hub of these protein networks. Accordingly, up‐regulation of HSP90 was observed in all Pt‐res cells and heat‐shock protein 90 alpha isoform knockout resensitizes Pt‐res cells to cisplatin (CDDP) treatment. Moreover, pharmacological HSP90 inhibition using two different inhibitors [17‐(allylamino)‐17‐demethoxygeldanamycin (17AAG) and ganetespib] synergizes with CDDP in killing Pt‐res cells in all tested models. Mechanistically, genetic or pharmacological HSP90 inhibition plus CDDP ‐induced apoptosis and increased DNA damage, particularly in Pt‐res cells. Importantly, the antitumor activities of HSP90 inhibitors (HSP90i) were confirmed both ex vivo in primary cultures derived from Pt‐res EOC patients ascites and in vivo in a xenograft model. Collectively, our data suggest an innovative antitumor strategy, based on Pt compounds plus HSP90i, to rechallenge Pt‐res EOC patients that might warrant further clinical evaluation. Abstract : By unbiased proteomics, we identified HSP90 as a central hub in platinum (Pt)‐resistant ovarian cancer models. Indeed, genetic and pharmacologial HSP90 inhibition sensitized resistant cells to CDDP treatment, potentiating DNA‐damage and apoptosis. Combined CDDP plus anti‐HSP90 therapy is effective also ex vivo on primary cultures from Pt‐resistant (Pt‐res) ovarian cancer patients and in vivo Pt‐res ovarian cancer xenograft mouse model.